Role of AI in Talent Management Strategy Implementation in Thailand Higher Education Sector - Chadchom Ratsameemonthon (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: This longitudinal study, derived from the Resource-Based View (RBV) theory, explores the relationship among training initiatives, adoption of Artificial Intelligence (AI), High-Performance Work Systems (HPWS), talent management practices (attraction, retention, learning, and development), and sustainable performance in higher education in Thailand. Methodology: Using a structured survey, 256 employees from several higher education institutions were surveyed over three wave periods. Findings: The overall findings suggest a significant and complex relationship among the antecedents to talent management and sustainable performance. Specifically, the study demonstrates the extent to which AI adoption positively influences sustainable performance through training programs and HPWS. Implications/Novel Contribution: This study contributes to theoretical and implications for RBV by demonstrating how human resources practices are dynamic to changing scenario and may be sustained for a competitive advantage. Moreover, the study has practical implications for leaders and policy makers of higher education sector now that they can see how technology and talent management should complement each other’s contributions to facilitate performance and sustainability.